2023
DOI: 10.7554/elife.81826
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic and noradrenergic axonal activity contains a behavioral-state signal that is coordinated across the dorsal cortex

Abstract: Fluctuations in brain and behavioral state are supported by broadly projecting neuromodulatory systems. In this study, we use mesoscale two-photon calcium imaging to examine spontaneous activity of cholinergic and noradrenergic axons in awake mice in order to determine the interaction between arousal/movement state transitions and neuromodulatory activity across the dorsal cortex at distances separated by up to 4 mm. We confirm that GCaMP6s activity within axonal projections of both basal forebrain cholinergic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 100 publications
6
28
0
Order By: Relevance
“…These findings are consistent with neuroimaging studies showing that changes in brain state lead to coordinated fluctuations of activity across the brain (Liu et al, 2018;Turchi et al, 2018;Setzer et al, 2022), and research that recorded simultaneously from neurons in cortical areas and subcortical areas such as the LC (Joshi and Gold, 2022;Collins et al, 2023). Furthermore, our results suggest that arousal-related fluctuations are more characteristic of neurons residing in the intermediate layers of the SC.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with neuroimaging studies showing that changes in brain state lead to coordinated fluctuations of activity across the brain (Liu et al, 2018;Turchi et al, 2018;Setzer et al, 2022), and research that recorded simultaneously from neurons in cortical areas and subcortical areas such as the LC (Joshi and Gold, 2022;Collins et al, 2023). Furthermore, our results suggest that arousal-related fluctuations are more characteristic of neurons residing in the intermediate layers of the SC.…”
Section: Discussionsupporting
confidence: 92%
“…1d). As expected based on previous studies [15][16][17][20][21][22] , we observed strong increases in ACh levels which tracked spontaneous locomoYon periods and the accompanying large pupil dilaYons (Fig. 1e).…”
Section: Experimental Setup and In Vivo Sensor Valida3onsupporting
confidence: 90%
“…Over the past decade, the mouse has served as an important model for understanding the mechanisms underlying these changes in state, which include neuromodulators 10 such as acetylcholine (ACh) [11][12][13][14] . Indeed, acYvity in cholinergic axons from the basal forebrain (BF) projecYng to the cortex is increased during whisking [15][16][17][18][19] , locomoYon [15][16][17][20][21][22] , and pupil dilaYon outside of exploratory periods 20,22 , and geneYcally-encoded ACh sensors have confirmed some of these effects 21,[23][24][25][26] . Axonal GCaMP acYvity might not have a straighiorward relaYonship to ACh levels, which depend on local release probabiliYes and clearance kineYcs, as well as the kineYcs of the fluorescent sensors themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Brain state was measured as the ratio between gamma power to delta power (cortical desynchrony). Facial movement of the vibrissae occurs throughout wake-sleep states and therefore, we used this face motion as a proxy for behavioral state similar to previous reports 52,54 . We found a strong relationship between cortical desynchrony and claustrum activity (R 2 =0.56, p<0.001, Figure 2K ) which was also present within individual sessions ( Figure S3M-N ).…”
Section: Resultsmentioning
confidence: 99%